Estudo farmacoepidemiológico de uso e prescrição de benzodiazepínicos em Teresina - Mendes, Cíntia Maria de Melo (2015)
Synthesized in the 50s, benzodiazepines (BZPs) quickly won physicians and patients for its apparent safety: few side effects and low toxicity. At the end of the 70s they began to be identified as harmful to health by the possibility of addiction. GENERAL PURPOSE: It featured the consumption of benzodiazepines in Teresina from a study of the medical criteria for their prescription and the characteristics of use by patients. BACKGROUND: According to the WHO, has about 400 million victims of mental disorders or psychosocial problems from the use licícitos or illegal psychoactive agents. Among these victims are those dependent on psychotropic above all BZPs, whereas the same figure among the best-selling drugs in the world, leading to behavior change and dependence. METHODOLOGY: descriptive epidemiological survey on the consumption of BZPs in Teresina, from prescriptive criteria analysis of physicians in offices and clinics of Teresina, the private network and their use by patients. RESULTS: It was found that the BZPs prescription is carried out by various experts and not only by psychiatrists. Gynecologists were large prescribers. Clonazepam was the most prescribed agent, 75.5% of doctors interviewed and also the most used by patients - 30.44%. The main medical reason for prescription was the relief of symptoms and complaints (66.9%). Doctors are covered for repetitive emissions requested by relatives, friends (77.55%) and several patients (95.51%). 67.10% of physicians attending this type of request made by patients and 62.10% of those made by friends and relatives. The recommendations provided by the medical profession mainly addressed dependence risk (27.19%). Medical rare warned about the risks of falling (2.92%) or cognitive impairment (4.60%). It was observed that women were the majority among the respondents - 80.4%, consuming benzodiazepines for anxiety, depression and insomnia. 65.3% of patients were prescribed always use the same médico.Pacientes BZPs for an average time of at least 15 months. Dependence is practically the only known risk to patients. Patients favor self-medication, sharing BZPs. There was affirmation of trial and purchase of benzodiazepines without prescription. CONCLUSION: The use of BZPs is widespread in prescription habits. Medical recommendations lack a basis in the current assigned risk to benzodiazepines. Most patients are unaware of risks of chronic use, except dependency. This knowledge does not limit or restrict consumption. There were reports without prescription buying and sharing drugs, self-medication.